Washed in Blood : Male Sacrifice, Trauma, and the Cinema - King, Claire Sisco (Book collections on Project MUSE., 2011)
Claire Sisco King offers an in-depth study of three prominent cycles of Hollywood films that follow the sacrificial narrative: the early-to-mid 1970s, the mid-to-late 1990s, and the mid-to-late 2000s. From Vietnam-era disaster movies to post-9/11 apocalyptic thrillers, she examines how each film represents traumatized American masculinity and national identity. What she uncovers is a cinematic tendency to position straight white men as America's most valuable citizens - and its noblest victims.